Analisa Persepsi Siswa/i SMK terkait Penerapan IPA (Fisika) dalam Bidang Kemaritiman - Lusiani (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2020)
The objective to be achieved in this study is to analyze the perceptions of vocational high school students regarding the application of science (physics) in the fields of maritime, medicine, and technology. The method in this research is a combination of survey and literature review. In this study the authors took the location at SMK Bina Bhakti Cilacap. Learning outcomes in the affective domain were obtained using a maritime study questionnaire. The instrument used was a maritime study questionnaire in the affective domain. Broadly speaking, data on the level of perception related to the application of Physics Science in the fields of maritime, medicine, and technology is obtained, which is 91% of the total. So it can be stated that almost some students have positive perceptions regarding the application of Physics Science in the fields of maritime, medicine, and technology. The analysis used is Descriptive Statistics Frequencies. Standard deviation comparison. The comparison results show that the empiric standard deviation (s = 1.982) is lower than the hypothetical standard deviation (σ = 5). This shows that the perception of vocational high school students regarding the application of science (physics) in the fields of maritime, medicine, and technology has a low variation. In other words, the perceptions of the subjects with one another are similar or uniform. Based on the analysis and discussion that has been carried out, it can be concluded that the perceptions of SMK students regarding the application of Science (physics) in the fields of Maritime, Medicine and Technology are similar or uniform. This means that vocational students generally have the same perception regarding the application of Science (physics) in the fields of Maritime, Medicine, and Technology.